Variability in physico-chemical characteristics of mango genotypes in northern Kerala - Pradeepkumar, T.; Johnkutty, I.; Philip, Joseph (Journal of Tropical Agriculture, 2007)
Physico-chemical properties of the fruits of 31 mango genotypes from north Kerala were evaluated. Based on the physical and chemical characteristics, these genotypes formed four homogenous clusters. Large table fruit varieties like ‘Mulgoa’, ‘Phirangiladua’, and ‘Banganapalli’ formed a single group, while ‘Bangalora’, ‘Gudad’, and ‘Chotta Jehangir’ deviated from that considerably. The highest significant correlation was noted between fruit length and pulp weight. Clustering pattern obtained in this study can be used for future genetic improvement of these cultivars.